Overcoming CAR-Mediated CD19 Downmodulation and Leukemia Relapse with T Lymphocytes Secreting Anti-CD19 T-cell Engagers - Blanco, Belén (Cancer Immunol Res, 2022)
Chimeric antigen receptor (CAR)–modified T cells have revolutionized the treatment of CD19-positive hematologic malignancies. Although anti-CD19 CAR-engineered autologous T cells can induce remission in patients with B-cell acute lymphoblastic leukemia, a large subset relapse, most of them with CD19-positive disease. Therefore, new therapeutic strategies are clearly needed. Here, we report a comprehensive study comparing engineered T cells either expressing a second-generation anti-CD19 CAR (CAR-T19) or secreting a CD19/CD3-targeting bispecific T-cell engager antibody (STAb-T19). We found that STAb-T19 cells are more effective than CAR-T19 cells at inducing cytotoxicity, avoiding leukemia escape in vitro, and preventing relapse in vivo. We observed that leukemia escape in vitro is associated with rapid and drastic CAR-induced internalization of CD19 that is coupled with lysosome-mediated degradation, leading to the emergence of transiently CD19-negative leukemic cells that evade the immune response of engineered CAR-T19 cells. In contrast, engineered STAb-T19 cells induce the formation of canonical immunologic synapses and prevent the CD19 downmodulation observed in anti-CD19 CAR-mediated interactions. Although both strategies show similar efficacy in short-term mouse models, there is a significant difference in a long-term patient-derived xenograft mouse model, where STAb-T19 cells efficiently eradicated leukemia cells, but leukemia relapsed after CAR-T19 therapy. Our findings suggest that the absence of CD19 downmodulation in the STAb-T19 strategy, coupled with the continued antibody secretion, allows an efficient recruitment of the endogenous T-cell pool, resulting in fast and effective elimination of cancer cells that may prevent CD19-positive relapses frequently associated with CAR-T19 therapies.